2022
DOI: 10.7759/cureus.28898
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Testing With Secondary Coinfection in Patients With COVID-19

Abstract: BackgroundThe coronavirus disease (COVID-19) virus has caused millions of deaths. It is difficult to differentiate between pure viral COVID-19 pneumonia and secondary infection. Clinicians often use procalcitonin (PCT) to decide on empiric antibiotic therapy. MethodologyWe performed a retrospective study of patients admitted with COVID-19 between January 1st, 2020, and June 30th, 2020. Patient demographics, clinical findings, and laboratory findings with a focus on PCT levels were recorded. Coinfection was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…Different from our results, a retrospective single-center study including COVID-19 patients admitted to the ICU (143 with and 99 without infection) in the first wave concluded that PCT values were not associated with positive cultures of respiratory and urine tracts, whereas they were increased in patients with bacteremia [28]. Indeed, the data showed higher values of PCT values in positive cultures compared to negative cultures, even in sputum (median 1.65 vs. 0 ng/mL; p < 0.01) and urine cultures (median 0.95 vs. 0.52 ng/mL; p < 0.01).…”
Section: Discussioncontrasting
confidence: 99%
“…Different from our results, a retrospective single-center study including COVID-19 patients admitted to the ICU (143 with and 99 without infection) in the first wave concluded that PCT values were not associated with positive cultures of respiratory and urine tracts, whereas they were increased in patients with bacteremia [28]. Indeed, the data showed higher values of PCT values in positive cultures compared to negative cultures, even in sputum (median 1.65 vs. 0 ng/mL; p < 0.01) and urine cultures (median 0.95 vs. 0.52 ng/mL; p < 0.01).…”
Section: Discussioncontrasting
confidence: 99%